Convicted male perpetrators’ narratives of their motivations for and experiences of perpetrating non-partner rape-femicide in the Western Cape, South Africa - Cook, Tricia (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.